Mitigating Physician Emigration in Nigeria by Improving the Internship Experience - Daniel, Faithful Miebaka; Essien, Emmanuel Aniekan; Gbuchie, Monica Anurika; Ukoaka, Bonaventure Micheal; Emeruwa, Victoria Ezinne (International Journal of Medical Students, 2023)
Nigeria faces a critical shortage of health workers, exacerbated by a growing of physician emigration. This study explored the negative internship experiences that drive Nigerian interns to migrate abroad, with a focus on the COVID-19 pandemic’s impact. Interns cite excessive workload and burnout, lack of professional development opportunities, challenging work environment, and mistreatment as key reasons for considering emigration. The COVID-19 pandemic has exacerbated these challenges, leading to shortages of personal protective equipment, limited screening services, and poor hazard allowances. The paper emphasizes the importance of adopting policies that make destination countries attractive to emigrating interns. These includes creating a supportive work environment with fair compensation, professional development opportunities, and adequate resources to retain interns in the country. It also highlights the significance of addressing mistreatment and bullying in the workplace. Collaboration between healthcare organizations, policy reforms, and increased healthcare financing are suggested as potential strategies to mitigate the brain drain and ensure a sustainable healthcare system in Nigeria. Improving internship conditions and addressing the shortcomings of managing the COVID-19 pandemic are essential to retaining Nigerian doctors and combatting physician emigration. This requires a coordinated effort from healthcare systems, policymakers, and stakeholders.